The killing consensus: police, organized crime, and the regulation of life and death in urban Brazil - Denyer Willis, Graham (University of California Press, 2015)
"We hold many assumptions about police work -- that it is the responsibility of the state, or that police officers be given the right to kill in the name of public safety or self-defense. But in The Killing Consensus, Graham Denyer Willis shows how in São Paulo, Brazil, killing and the arbitration of 'normal' killing in the name of social order is actually conducted by two groups--the police and organized crime--both operating by parallel logics of murder. Based on three years of ethnographic fieldwork, Willis traces how homicide detectives categorize two types of killing: the first resulting from 'resistance' to police arrest (which is often broadly defined), and the second at the hands of a crime 'family' known as the Primeiro Comando da Capital (PCC). Death at the hands of police happens regularly, while the PCC's centralized control and strict moral code among criminals has also routinized killing, ironically making the city feel safer for most residents. In a fractured urban security, where killing mirrors patterns of inequitable urbanization and historical exclusion on class, gender and racial lines, Denyer Willis' research finds that the city's cyclical periods of peace and violence can best be understood through an unspoken but mutually observed consensus on the right to kill. This consensus hinges on common notions and street level practices of who can die, where, how, and by whom, revealing an empirically distinct configuration of authority that Denyer Willis calls sovereignty by consensus"--Provided by publisher